Peningkatan Keterampilan Berbicara Bahasa Indonesia Melalui Teknik Bercerita Bergambar Pada Siswa Kelas 1: Keterrampilan Berbicara Bahasa Indonesia - Siti Nur Aisyah; Navandra Berliana Fitri; nda Laurenza Nailis; Sekar Dwi Ardianti (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
This study identified the low speaking skills of first grade elementary school students as a crucial problem that needs to be addressed. Initial observations showed that students often had difficulty in conveying ideas or thoughts orally; they were often unable to speak coherently, clearly, and even showed a lack of confidence when asked to communicate in front of the class or with their friends. This study was designed with the main objective of improving students' Indonesian speaking skills through the application of picture storytelling techniques. The method used in this study was Classroom Action Research (CAR) which was carried out in two cycles. Each cycle consisted of four stages, namely planning, implementing actions, observation, and reflection. Data collection was carried out through observation, interviews, documentation, and speaking skills tests. The data analysis technique was carried out quantitatively descriptively by calculating the percentage increase in the completion of speaking skills from each cycle. The results of this study showed that before the actions were implemented, the initial condition of students' speaking skills was relatively low, reaching 55%. This figure clearly indicates a serious problem in mastering oral language skills. However, after the intervention in cycle I, there was a pleasing increase, the average student speaking skills rose to 63%, and further reached 66% at the second meeting of cycle I. A much more drastic and proud increase was seen in cycle II, where the average value of students' speaking skills jumped to 88%, and the peak even reached 98% at the final meeting. These strong quantitative data convincingly prove that the application of picture storytelling techniques is very effective in significantly improving the speaking skills of first grade elementary school students.